ETHNOMATHEMATICS: THE CONSTRUCTION OF PEDATI GEDE CIREBON AND THE POTENTIAL OF ITS INTEGRATION IN MATHEMATICS LEARNING - Imam Saparudin; Benny Anggara; Atikah Nuril Huda; Indri Zakiah Awaliyah; Maman Tasman (State Islamic University of North Sumatra, 2023)
This study aims to reveal the mathematical activities in the construction of Pedati Gede Cirebon and the potential for its integration into mathematics learning through ethnomathematics exploration. This study follows a qualitative research method with a qualitative verification research design to obtain a clear picture of the relationship between the technology used and the mathematical activities. The data collection techniques include observation, interviews, and material review. Based on the data collected and analyzed, it was found that mathematical activities can be seen in several depictions of existing technology, especially in the construction of large wheels. The designer of Pedati Gede Cirebon hopes for a large mechanical advantage for energy efficiency when operating it. This mechanical advantage is closely related to the concept of comparison in junior high school mathematics learning, so it can be used as a context for learning the concept of comparison to make it more meaningful. Several other mathematical concepts in the mathematical activities and construction of Pedati Gede Cirebon are the concept of circles and linear equations. The circle is related to the pillars of the wheel as support, while the concept of linear equations is used in determining certain quantities in several sizes available in the construction of Pedati Gede Cirebon.